2013
DOI: 10.1177/0956462413513748
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fish oil on lipid profile and other metabolic outcomes in HIV-infected patients on antiretroviral therapy: a randomized placebo-controlled trial

Abstract: Although antiretroviral therapy has revolutionized the care of HIV-infected patients, it has been associated with metabolic abnormalities. Hence, this study was planned to investigate the effects of fish oil on lipid profile, insulin resistance, and body fat distribution in HIV-infected Brazilian patients on antiretroviral therapy, considering that marine omega-3 fatty acids seem to improve features of the metabolic syndrome. We conducted a randomized, parallel, placebo-controlled trial that assessed the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 20 publications
1
15
0
4
Order By: Relevance
“…The same thing happens with the initial triglicerides dosage 15,16 . New clinical trials were published [16][17][18] , and better answers are necessary to the questions mentioned above.…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…The same thing happens with the initial triglicerides dosage 15,16 . New clinical trials were published [16][17][18] , and better answers are necessary to the questions mentioned above.…”
Section: Introductionmentioning
confidence: 70%
“…Omacor® -3360 mg 26,29 ; Maxepa® -2700 mg 25 ,1800 mg 27 ; Lovaza® -3360 mg 18 ; Coromega® -2900 mg 28 ; Salmon oil -900 mg 15 ; Fish oil -4000 mg 17 , 900 mg 16 The studies included in this revision are shown in Chart 1. Year variables, classification of Jadad et al 19 , EPA and DHA dosage and initial triglycerides were analyzed to evaluate heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations